Discoidin domain receptor 2 is an important modulator of BMP signaling during heterotopic bone formation - Fashuai Wu; Chunxi Ge; Haichun Pan; Yuanyuan Han; Yuji Mishina; Vesa Kaartinen; Renny T. Franceschi (Bone Research)
Abstract Bone morphogenetic proteins are essential for bone regeneration/fracture healing but can also induce heterotopic ossification (HO). Understanding accessory factors modulating BMP signaling would provide both a means of enhancing BMP-dependent regeneration while preventing HO. This study focuses on the ability of the collagen receptor, discoidin domain receptor 2 (DDR2), to regulate BMP activity. As will be shown, induction of bone formation by subcutaneous BMP2 implants is severely compromised in Ddr2-deficient mice. In addition, Ddr2 deficiency attenuates HO in mice expressing the ACVR1 mutation associated with human fibrodysplasia ossificans progressiva. In cells migrating into BMP2 implants, DDR2 is co-expressed with GLI1, a skeletal stem cell marker, and DDR2/GLI1-positive cells participate in BMP2-induced bone formation where they contribute to chondrogenic and osteogenic lineages. Consistent with this distribution, conditional knockout of Ddr2 in Gli1-expressing cells inhibited bone formation to the same extent seen in globally Ddr2-deficient animals. This response was explained by selective inhibition of Gli1 + cell proliferation without changes in apoptosis. The basis for this DDR2 requirement was explored further using bone marrow stromal cells. Although Ddr2 deficiency inhibited BMP2-dependent chondrocyte and osteoblast differentiation and in vivo, bone formation, early BMP responses including SMAD phosphorylation remained largely intact. Instead, Ddr2 deficiency reduced the nuclear/cytoplasmic ratio of the Hippo pathway intermediates, YAP and TAZ. This suggests that DDR2 regulates Hippo pathway-mediated responses to the collagen matrix, which subsequently affect BMP responsiveness. In summary, DDR2 is an important modulator of BMP signaling and a potential therapeutic target both for enhancing regeneration and treating HO.